2016
DOI: 10.36233/0372-9311-2016-4-55-60
|View full text |Cite
|
Sign up to set email alerts
|

Condition of Anti-Measles Immunity in Patients on Waiting-List for Lung Transplantation

Abstract: Aim. Determination of intensity of immunity against measles in patients on waiting-list for lung transplantation. Materials and methods. IgG levels against measles virus were studied in blood sera of 80 adult patients (mean age 35.8± 11.4 years) on waiting-list of lung transplantation, without history of this disease. Determination of IgG levels against measles virus was carried out by ELISA using a standard kit from «Vektor-Best» (VectoMeasles-IgG). Results. Protective level of IgG against measles virus (abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The analysis of the laboratory results of the study in which 1742 people aged 25-67 years (403 men and 1339 women) were involved, showed that the median of IgG antibodies level to measles virus in samples was 1.2 (0.4-3.2) IU/ mL; the proportion of seronegative respondents was 15 [14][15][16][17]%. Without taking into account the age of the respondents between men and women, no statistically significant differences were found neither in the level of IgG antibodies (1.07 (0.4; 3.0) IU/mL in the group of men and 1.3 (0.4; 3.3) IU/mL in the group of women (U = 1.15, p = 0.28)), nor in the part of seronegative respondents (13 [10-17]% (54/403) among men and 16 [14][15][16][17][18]% (214/1339) among women (χ 2 = 1.6, p = 0.21)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of the laboratory results of the study in which 1742 people aged 25-67 years (403 men and 1339 women) were involved, showed that the median of IgG antibodies level to measles virus in samples was 1.2 (0.4-3.2) IU/ mL; the proportion of seronegative respondents was 15 [14][15][16][17]%. Without taking into account the age of the respondents between men and women, no statistically significant differences were found neither in the level of IgG antibodies (1.07 (0.4; 3.0) IU/mL in the group of men and 1.3 (0.4; 3.3) IU/mL in the group of women (U = 1.15, p = 0.28)), nor in the part of seronegative respondents (13 [10-17]% (54/403) among men and 16 [14][15][16][17][18]% (214/1339) among women (χ 2 = 1.6, p = 0.21)).…”
Section: Resultsmentioning
confidence: 99%
“…In the age group 40-49 years old, the proportion of seronegative women is statistically significantly higher than the proportion of seronegative men: 22 [18][19][20][21][22][23][24][25][26]% and 11 [6][7][8][9][10][11][12][13][14][15][16][17][18]%, respectively (χ 2 = 7.0, p = 0.001).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation